The case for Parentalism at work: balancing feminist care ethics and justice ethics through a Winnicottian approach : a school case study - Edwards, Michaela (Journal of business ethics, 2024)
Using an ethnographic case study based in a UK state school for 11- to 18-year-olds, this paper explores the tensions that arose when the senior leadership team (SLT) introduced a justice-based ethic-of-care that prioritized good grades and equal treatment for all pupils over a feminist ethic-of-care (preferred by most teachers in non-leadership roles) that accentuated individual pupil need and placed greater emphasis on a broader social education. Through highlighting the tensions between a feminist ethic-of-care and a more "masculine" style, justice-based approach to care-ethics, the paper extends the organisational care-ethics literature. We emphasise that such tensions occurred whether the different ethics were enacted by men, women, or non-binary individuals. In order to better understand the tensions between these two ethical approaches, we draw upon the theoretical work of Donald Winnicott, which highlights the importance both of maternal and paternal roles during infancy. We update Winnicott's ideas, noting how maternal and paternal caring roles can be undertaken by people of varied gender identities. Building on Winnicott's theory, we propose a new "Parentalist" ethic-of-care, which has the potential to balance and hold together ideas of both a feminist ethic-of-care, and a justice-based ethic. A Parentalist ethic-of-care could support teachers yet recognize the context of the contemporary neo-liberal environment, where most children need to attain formal qualifications in a marketized world, and where such measures of success are highly valued.